(untitled) (Eurasian Medical Research Periodical, 2023)
Systemic sclerosis is a chronic autoimmune inflammatory disease of connective tissue with multi-syndrome clinical presentation.Disease-related factors,age,hormone therapy may be associated with increased bone loss. Skeletal damage is considered to be one of significant contributors to the quality of life of these patients. The prognosis of the disease is determined by the nature and severity lesions the thoracic organs ,especially the branches and the heart. The goal of this study was to determine the prevalence of osteoporosis and associated fractures in people with systemic sclerosis. 58of publication and 18 patients were selected for which the study of mineral bones with systematic sclerosis and in the control group of healthy people in comparison groups that included other rheumatic disease. Studies were conducted in relatively small groups of patients;the results presented vary over a wide range.Further studies are required to clarify the mechanisms of osteoporosis development and its treatment and prevention in patients with systemic sclerodermia